Lee–Carter Mortality Forecasting - Ignatavičiūtė, Eglė; Mikalauskaitė-Arminienė, Rasa; Šiaulys, Jonas (Lithuanian Journal of Statistics, 2012)
In this paper, we focus on Lee–Carter mortality forecasting. Model residuals and future mortality trendsare explored. Predictions of the force of mortality for France, Belarus and Lithuania are provided and compared. Severalmodifications of the model are applied to Lithuanian mortality data in order to obtain the most precise forecast.